Cytomegalovirus (CMV)-associated portal vein thrombosis in a healthy, immunocompetent man. Issue 12 (28th December 2020) - Burkey, Caroline; Teng, Catherine; Hussein, Khalil Ian; Sabetta, James
Abstract : We present a previously healthy man in his 30s who presented with typical viral prodrome symptoms and worsening abdominal pain. He was found to have portal vein thrombosis, with extensive hypercoagulability workup performed. It was determined that the aetiology of thrombus was secondary to acute cytomegalovirus infection. The patient was started on anticoagulation therapy, with later clot resolution demonstrated on abdominal Doppler ultrasound and abdominal CT scan. Given the atypical presentation of this common virus, we performed a literature review of cytomegalovirus-associated portal vein thrombosis in healthy individuals; we found that most patients present with non-specific symptoms of fever and abdominal pain in the setting of a viral prodrome. This case and literature review suggest physicians must consider cytomegalovirus-associated portal vein thrombosis as a potential diagnosis when patients present with abdominal pain and viral symptoms. The literature highlights the need for a consensus on anticoagulation and antiviral therapy.